IMPLEMENTING COMMUNICATIVE APPROACH IN TEACHING SPEAKING - Alinda, Marta (Universitas Islam Balitar, 2019)
This study focused on investigating types of teaching techniques used by English lecturers in teaching speaking and how the implementation types of teaching techniques in teaching speaking under the guidelines of three questions: (1) What types of teaching techniques are used by the English lecturers in teaching speaking? (2) Why do they apply techniques in teaching learning process of speaking? (3) How are the implementation types ofteaching techniques in the teaching learning process of speaking?This research was conducted using descriptive qualitative research. Descriptive qualitative method was chosen because this research dealt with words not number. Besides, the data were described descriptively in the form of paragraph. The data analysis revealed some findings covering the formulation of the research questions.The result of the study showed thatspeech technique was performed by lecturers in teaching speaking that students were really enthusiast during teaching and learning process through speech. Speech also can increase students’ speaking skill. The result of the study could be used to increase teaching and learning process of speaking in order to improve speaking skills.